2016
DOI: 10.1302/0301-620x.98b9.38057
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage treatment of chronic osteomyelitis with a new absorbable, gentamicin-loaded, calcium sulphate/hydroxyapatite biocomposite

Abstract: This single-stage protocol, facilitated by the absorbable local antibiotic, is effective in the treatment of chronic osteomyelitis. It offers a more patient-friendly treatment compared with other published treatment options. Cite this article: Bone Joint J 2016;98-B:1289-96.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
207
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(228 citation statements)
references
References 41 publications
8
207
5
1
Order By: Relevance
“…Eight of the 10 cases healed with a single operation and all 10 remained infection-free at final review 65.…”
Section: Oxford Protocol For Dead Space Management With Ceramic Biocomentioning
confidence: 95%
See 1 more Smart Citation
“…Eight of the 10 cases healed with a single operation and all 10 remained infection-free at final review 65.…”
Section: Oxford Protocol For Dead Space Management With Ceramic Biocomentioning
confidence: 95%
“…The only study investigating a commercially available biphasic cement showed a lower infection recurrence rate of 4% 65. This large study included patients with poor Cierny & Mader (C-M) hosts and Type III and IV chronic osteomyelitis, infected non-union and concomitant septic arthritis.…”
Section: Outcomes In the Use Of Ceramic Antibiotic Carriersmentioning
confidence: 99%
“…The use of RBGS mixed with vancomycin has been shown to be a successful outcome in the management of chronic osteomyelitis and non-union in adults [28, 29]. McNally MA et al described effective results in the treatment of deep bone infection using a new antibiotic-loaded biocomposite in the eradication of infection from bone defects [30]. Also, a systematic review of 15 studies to access the utility of anti-infective bone graft substitutes in osteomyelitis treatment suggested that such treatment could be a good option [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of a calcium sulfate/hydroxyapatite composite with local antibiotic gentamicin (CERAMENT™ G, Bonesupport, Lund, Sweden) seemed to be a reasonable alternative. So far, the applied BGS in our case has been used in bone reconstruction after osteomyelitis [20], but not in spine surgery. The composite enabled us to combine posterior debridement, posterior stabilization, and filling of the intervertebral space in a one-stage procedure.…”
Section: Discussionmentioning
confidence: 99%